2004
DOI: 10.1111/j.0031-9317.2004.0173.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photosynthesis by heat stress: the activation state of Rubisco as a limiting factor in photosynthesis

Abstract: Although the catalytic activity of Rubisco increases with temperature, the low affinity of the enzyme for CO(2) and its dual nature as an oxygenase limit the possible increase in net photosynthesis with temperature. For cotton, comparisons of measured rates of net photosynthesis with predicted rates that take into account limitations imposed by the kinetic properties of Rubisco indicate that direct inhibition of photosynthesis occurs at temperatures higher than about 30 degrees C. Inhibition of photosynthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
420
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 590 publications
(449 citation statements)
references
References 55 publications
(101 reference statements)
22
420
3
4
Order By: Relevance
“…Previously, elevated temperatures were shown to negatively affect photosynthesis (Feller et al, 1998;Law and Crafts-Brandner, 1999;Haldimann and Feller, 2004), influencing leaf metabolism primarily through Rubisco activase properties and Rubisco activation state (Feller et al, 1998;Crafts-Brandner and Salvucci, 2000;Feller, 2004, 2005). It was also demonstrated that plants increase stomatal conductance under high temperatures (Salvucci and Crafts-Brandner, 2004). However, our results show that stomatal response to heat and drought is complex: legumes respond to moderate stress by closing stomata or causing irregular conductance and to high temperature stress by increasing stomatal conductance, even under drought.…”
Section: Resultssupporting
confidence: 45%
“…Previously, elevated temperatures were shown to negatively affect photosynthesis (Feller et al, 1998;Law and Crafts-Brandner, 1999;Haldimann and Feller, 2004), influencing leaf metabolism primarily through Rubisco activase properties and Rubisco activation state (Feller et al, 1998;Crafts-Brandner and Salvucci, 2000;Feller, 2004, 2005). It was also demonstrated that plants increase stomatal conductance under high temperatures (Salvucci and Crafts-Brandner, 2004). However, our results show that stomatal response to heat and drought is complex: legumes respond to moderate stress by closing stomata or causing irregular conductance and to high temperature stress by increasing stomatal conductance, even under drought.…”
Section: Resultssupporting
confidence: 45%
“…High temperature result in the decreased solubility of O 2 and CO 2 however, increased photorespiration and lower photosynthesis is the result of increased level of CO 2 than O 2 [71]. In addition, decreased activity of Rubisco at high temperature is primarily due to inhibition of the enzyme Rubisco activase which becomes unable to overcome the inherently faster rates of Rubisco inactivation [72][73][74]. Amongst the photosynthetic apparatus photosystem II being more tolerant to drought stress than heat relatively plays a key role in leaf photosynthesis [75].…”
Section: Effects Of Heat Stress On Plant Physiologymentioning
confidence: 99%
“…This technology will extend our knowledge about PSI and the cooperation between PSI and PSII and give us a more thorough and comprehensive picture about the operating mechanisms of plant photosynthetic apparatus Yan et al 2012). It is noticeable that CO 2 fixation process is also a critical step for photosynthesis (Salvucci and Crafts-Brandner 2004). Rubisco enzyme and its activation enzyme play a key role in this step, and their activities and contents can be measured, but the procedure is relatively complex.…”
Section: Plant Biomass and Photosynthesismentioning
confidence: 99%